2022
DOI: 10.3390/jpm12050797
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Chronic Pain: What Do Patients Discuss?

Abstract: A high number of online support groups have been created on social media platforms to reinforce personal empowerment and social support. The goal of this study was to perform natural language processing by constructing a bag-of-words model and conducting topic modelling based on posts extracted from a chronic pain community. The subreddit called ‘r/sChronicPain’ was used to investigate communication on social media platforms for chronic pain patients. After data cleaning and lemmatisation, a word cloud was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Despite this, social media and YouTube videos, both of which are Internet-based resources, were reported to be used by 34% and 26% of respondents, respectively, and rated relatively high in helpfulness (both 2/5, where 1 reflects the highest helpfulness rating). Social media provides a platform for connecting and exchanging thoughts and experiences with others in a similar situation (Goudman et al, 2022), and this type of engagement has been found to increase general well-being, a user’s sense of control and belonging (Barak et al, 2008). Furthermore, YouTube videos often provide pain education in plain language with vivid animation, enhancing the overall experience of users, and may increase their perceived helpfulness (Heathcote et al, 2019; Machado et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, social media and YouTube videos, both of which are Internet-based resources, were reported to be used by 34% and 26% of respondents, respectively, and rated relatively high in helpfulness (both 2/5, where 1 reflects the highest helpfulness rating). Social media provides a platform for connecting and exchanging thoughts and experiences with others in a similar situation (Goudman et al, 2022), and this type of engagement has been found to increase general well-being, a user’s sense of control and belonging (Barak et al, 2008). Furthermore, YouTube videos often provide pain education in plain language with vivid animation, enhancing the overall experience of users, and may increase their perceived helpfulness (Heathcote et al, 2019; Machado et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that patients with chronic pain may be able to overcome the stigma and invisibility of persistent pain through mutual online empowerment ( 26 ). For example, the possibility of being visible and of having unlimited opportunities for conversation with a wider audience may have important positive effects ( 27 , 28 ).…”
Section: Open Data Helping Ubiquitous Communities Of People Living Wi...mentioning
confidence: 99%
“…Speci cally, regarding health-related applications, various works started to focus on mental health due to its close relation with language, such as depression diagnosis [9], suicidal ideation detection [10], and the linguistic analysis of multiple and cooccurring mental health conditions [11]. Indeed, some works have focused on computationally exploring language for chronic pain, such as, extracting biomedical entities and relations from disease speci c online forums [12], importance analysis of latent topics (as pre-de ned by the authors, as opposed to automatically extracted) in online discussions of In ammatory Bowel Disease [13], qualitative analysis of the concerns of women with Rheumatoid Arthritis, according to textual submissions to Reddit on speci c sub-forums related to this disease [14], and topic modelling over the Reddit's sub-forum ChronicPain to analyze common semantic structures of chronic pain online reports, discovering that back pain is, by far, the most mentioned [15].…”
Section: Introductionmentioning
confidence: 99%